A comunicação de pensamentos sutis: a importância da dimensão de não-consciência nas estratégias de comunicação no contemporâneo - Reinert, Leila (2012)
The cognizance of the last fifty years mental processes, via the sciences of the mind, has vastly expanded the understanding of the brain s mechanisms that produce, control and manage human subjectivity. People s sensibility, affections and feelings, hitherto kept in separate, distinct areas, now belong to the ordinary everyday world. This dissertation seeks to understand how the communication of the sensitive, of the subtle thoughts, circulates in contemporary times. Taking into account consciousness studies, a sense of self and the unconscious processes that relate to the conscious thought, there is an indication of the non-conscience problem the border that separates and overlap conscious and unconscious. To analyze this threshold phenomenon, it is necessary to review the perceptual processes highly regarded by philosophy, used by art and charted by the sciences of the mind. There is also an appropriation of the sensitive by the so-called Cognitive capitalism , that indicates the need to circulate in a clearer fashion between the unconscious sensations and the conscious perceptions, and of a greater subjective flexibility. This dissertation intends to point out the importance of awareness of the non conscious processes in the visual communication of subtle thoughts when working with memory, perception, the learning process and language in cerebral and the mind s cognitive processes. It is through Design that research explores the concrete examples of this delicate communication. The affection, the sensibility, the emotions contained within the production and reception of the information circulating nowadays and that, above all, condition behavior, are key to the understanding of life in the contemporary